Evaluating Maternity Units: a prospective cohort study of freestanding midwife-led primary maternity units in New Zealand—clinical outcomes. Issue 8 (29th August 2017) - Grigg, Celia P; Tracy, Sally K; Tracy, Mark; Daellenbach, Rea; Kensington, Mary; Monk, Amy; Schmied, Virginia
Abstract : Objective: To compare maternal and neonatal birth outcomes and morbidities associated with the intention to give birth in a freestanding primary level midwife-led maternity unit (PMU) or tertiary level obstetric-led maternity hospital (TMH) in Canterbury, Aotearoa/New Zealand. Design: Prospective cohort study. Participants: 407 women who intended to give birth in a PMU and 285 women who intended to give birth at the TMH in 2010–2011. All of the women planning a TMH birth were 'low risk', and 29 of the PMU cohort had identified risk factors. Primary outcomes: Mode of birth, Apgar score of less than 7 at 5 min and neonatal unit admission. Secondary outcomes: labour onset, analgesia, blood loss, third stage of labour management, perineal trauma, non-pharmacological pain relief, neonatal resuscitation, breastfeeding, gestational age at birth, birth weight, severe morbidity and mortality. Results: Women who planned a PMU birth were significantly more likely to have a spontaneous vaginal birth (77.9%vs62.3%, adjusted OR (AOR) 1.61, 95% CI 1.08 to 2.39), and significantly less likely to have an instrumental assisted vaginal birth (10.3%vs20.4%, AOR 0.59, 95% CI 0.37 to 0.93). The emergency and elective caesarean section rates were not significantly different (emergency: PMU 11.6% vs TMH 17.5%, AOR 0.88, 95% CI 0.55 to 1.40; elective: PMU 0.7% vs TMH 2.1%, AOR 0.34, 95% CI 0.08 to 1.41). There were no significant differences between the cohorts in rates of 5 min Apgar score of <7 (2.0%vs2.1%, AOR 0.82, 95% CI 0.27 to 2.52) and neonatal unit admission (5.9%vs4.9%, AOR 1.44, 95% CI 0.70 to 2.96). Planning to give birth in a primary unit was associated with similar or reduced odds of intrapartum interventions and similar odds of all measured neonatal well-being indicators. Conclusions: The results of this study support freestanding midwife-led primary-level maternity units as physically safe places for well women to plan to give birth, with these women having higher rates of spontaneous vaginal births and lower rates of interventions and their associated morbidities than those who planned a tertiary hospital birth, with no differences in neonatal outcomes.